Fungi Preference of Fungivorous Nematode Aphelenchus avenae (Aphelenchida: Aphelenchidae) and Its Impact on Strawberry (Fragaria ananassa Duch.) Root - Xingyue Li; Shuocheng Zeng; Jun Yi; Haiting Zhang; Huijuan Fu; Cheng Chen; Qizhi Liu; Aocheng Cao; Wuyun Yang (Agriculture)
In continuously cropped strawberry soil, a large population of the fungivorous nematode, Aphelenchus avenae, was observed to increase significantly over time. This nematode, which feeds on pathogenic fungi affecting strawberries, has significant potential as a biocontrol agent. The purpose of this article is to discuss the nematode’s preference for fungi associated with strawberries and its impact on the growth of strawberry roots. With the exception of Trichoderma harzianum, most of the pathogenic fungi commonly found in strawberry soil, such as Fusarium oxysporum, Rhizoctonia solani, Verticillium, Phytophthora infestans, and Botrytis cinerea Pers. attracted A. avenae and supported their propagation. All treatments with A. avenae and the non-nematode control showed a consistent trend throughout strawberry development, indicating that a moderate amount of A. avenae does not adversely affect strawberry roots. Moderate and low levels of A. avenae significantly increased the activity of antioxidant enzymes, superoxide dismutase (SOD), and peroxidase (POD) in strawberry roots in all treatments during the entire growth stages. Also, the malondialdehyde (MDA) content of strawberry roots in all nematode treatments was lower than that in the no-nematode control. Despite an overabundance of A. avenae, which negatively affected the redox system balance of strawberry roots, A. avenae can protect the roots from pathogenic fungi by preventing infection and damage. These results lay the foundation for the potential use of A. avenae as a biological agent to control these pathogenic fungi in strawberry soil, in combination with the biological fungi (T. harzianum).